Sharia Management Strategy in Ensuring the Feasibility of Busmini Business in Labang District as an Alternative to Public Transportation - Safiratunnisa’ Ansari Putri; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
Transportation is a vital need to support community activities, but not all areas have access to adequate public transportation. This study aims to analyze sharia management strategies to ensure the feasibility of an alternative transportation business, Busmini, managed by a husband and wife in Labang District. The approach used was a qualitative case study method, through in-depth interviews, observation, and documentation. The results show that this business applies sharia-based management principles such as mudharabah and ijarah, emphasizing the values of trust, honesty, and social responsibility. The feasibility of the business is evident in its simple financial recording system, informal profit-sharing model, and tangible contribution to the local economy through the provision of jobs and affordable transportation services. The implemented management strategies not only ensure business sustainability but also reflect the integration of Islamic values and micro-business practices. This research is expected to serve as a reference for MSMEs in developing businesses oriented towards blessings and welfare.